Karakterisasi, Aktivitas Antioksidan dan Komponen Bioaktif Bulu Babi (Diadema savignyi) dari Perairan Pantai Trikora Tiga Pulau Bintan - Azwin Apriandi; Raja Marwita Sari Putri; Irvan Tanjung (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Sea urchin is one type of aquatic biota that comes from echinoderms phylum. Biota is very abundant along the beach Trikora Bintan Island. This study aims to characterize and analyze the antioxidant activity and bioactive components contained in the crude extract of hexan and methanol sea urchins. Based on the results of this study, this biota has yield shell, thorn, viscera and gonad that is 42.62%, 18.07%, 27.31% and 12%. The result of extract of crude extract of intact fur with methanol (UMeOH), whole with hexan (UHx), gonad with methanol (GMeOH) and gonad with hexan (GHx) obtained yield of 2.37%, 3.19%, 9.87% and 6.06%. result of bioactive component analysis got 5 kinds of bioactive among them alkaloid, steroid, flavonoid, saponin and phenol hidroquinon. Analysis of antioxidant activity of crude extract of pig bristle with DPPH method obtained results for UMeOH, UHx, GMeOH and GHx is 3003 ppm, 3508 ppm, 1485 ppm dan 1420 ppm.